1998
DOI: 10.1007/s002140050390
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of ammonia with propane and cyclopropane: electrostatic guidelines for ab initio treatment

Abstract: A model based on the molecular electrostatic potential (MESP) is employed for the investigation of structures and energies of complexes of ammonia with propane and cyclopropane. The electrostatic model geometries are employed as starting points for an ab initio investigation at the self-consistent ®eld and second-order Mùller-Plesset (MP2) levels. The most stable structures of C 3 H 6 ..NH 3 and C 3 H 8 ..NH 3 complexes have the interaction energies of 10.07 kJ/mol and 8.15 kJ/mol, respectively, at the MP2/6-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…[17][18][19] A remarkable feature of this technique is that it can be applied for weakly bonded complexes. 20 This approach was subsequently used by Gadre et al [21][22][23][24] to elucidate the nature and strength of the bonding involved. Recently, Ragevendra and Arunan have utilized this method to identify regions of high electron density in CH 4 9 and now it is well known that the tetrahedral face of methane has an electron-rich centre and can act as a hydrogen bond accep tor.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] A remarkable feature of this technique is that it can be applied for weakly bonded complexes. 20 This approach was subsequently used by Gadre et al [21][22][23][24] to elucidate the nature and strength of the bonding involved. Recently, Ragevendra and Arunan have utilized this method to identify regions of high electron density in CH 4 9 and now it is well known that the tetrahedral face of methane has an electron-rich centre and can act as a hydrogen bond accep tor.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it has been shown 32b that the incorporation of electron correlation does not alter the CP characteristics at this level of basis. Our earlier investigation 33 has also concluded that the inclusions of diffuse basis functions in the above basis (6-31++G(d,p)) do not change the energy ranking of the structures of the hydrogen-bonded complexes.…”
Section: Discussionmentioning
confidence: 86%
“…In a recent work, , we have carried out the Kitaura-Morokuma 31 interaction energy decomposition analysis for similar types of complexes, viz. C 3 H 6 ··· NH 3 and C 3 H 8 ··· NH 3 .…”
Section: Discussionmentioning
confidence: 99%
“…44 Particularly, the site of metal cation binding confirms the electron localization in the corresponding region of a molecular system. 40 Molecular electrostatic potential (MESP) is a scalar field, used extensively 38, [45][46][47] in the literature for exploring reactivity patterns of molecules and their noncovalent interactions. Particularly, it is a well-recognized property for investigating the sites for electrophilic attack.…”
Section: Introductionmentioning
confidence: 99%